Factors Related to Migraine Patients’ Decisions to Initiate Behavioral Migraine Treatment Following a Headache Specialist’s Recommendation: A Prospective Observational Study - Minen, Mia T (Pain Med, 2018)
OBJECTIVE: To evaluate the frequency with which migraine patients initiated behavioral migraine treatment following a headache specialist recommendation and the predictors for initiating behavioral migraine treatment. METHODS: We conducted a prospective cohort study of consecutive patients diagnosed with migraine to examine whether the patients initiated behavioral migraine treatment following a provider recommendation. The primary outcome was scheduling the initial visit for behavioral migraine treatment. Patients who initiated behavioral migraine treatment were compared with those who did not (demographics, migraine characteristics, and locus of control) with analysis of variance and chi-square tests. RESULTS: Of the 234 eligible patients, 69 (29.5%) were referred for behavioral treatment. Fifty-three (76.8%) patients referred for behavioral treatment were reached by phone. The mean duration from time of referral to follow-up was 76  (median 76, SD = 45) days. Thirty (56.6%) patients initiated behavioral migraine treatment. There was no difference in initiation of behavioral migraine treatment with regard to sex, age, age of diagnosis, years suffered with headaches, health care utilization visits, Migraine Disability Assessment Screen, and locus of control (P > 0.05). Patients who had previously seen a psychologist for migraine were more likely to initiate behavioral migraine treatment than patients who had not. Time constraints were the most common barrier cited for not initiating behavioral migraine treatment. CONCLUSIONS: Less than one-third of eligible patients were referred for behavioral treatment, and only about half initiated behavioral migraine treatment. Future research should further assess patients’ decisions regarding behavioral treatment initiation and methods for behavioral treatment delivery to overcome barriers to initiating behavioral migraine treatment.